Comparison of Immunohistochemical Expression of DNMT3B among Oral, Laryngeal and Skin SCC - Khaled J. Abed; Wasan H. Younis (College of Dentistry/ University of Baghdad, 2016)
Background: Recently epigenetic alterations have received increased attention because of theirimportant role in the process of tumerigenesis. It has been found that more than half of genetic changes were epigenetic. Epigenetic alterations are catalyzed by DNMTs enzymes. Increased knowledge about this molecular event may achieve progress in the war against cancer. The aim of this study was to evaluate and compare the expression of DNMT3B among oral, laryngeal and skin SCC. Materials and Methods: This study was performed on (120) formalin-fixed, paraffin-embedded blocks, histopathologically diagnosed as oral, laryngeal and skin SCC). Immunohistochemical staining of DNMT3B antibody was performed on each case of this study. Results: The immunohistochemical analysis showed that the DNMT3b is over expressed in oral, laryngeal and skin squamous cell carcinoma as (77.5%), (77.5%) and (72.5%) respectively, withsignificant difference in expression among them (P=0.009), The expression in all the three types is correlated positively with the degree of differentiation (P